2009 International Conference on Advanced Information Networking and Applications Workshops 2009
DOI: 10.1109/waina.2009.41
|View full text |Cite
|
Sign up to set email alerts
|

The Small-World Model for Amino Acid Interaction Networks

Abstract: In this paper we introduce the notion of protein interaction network. This is a graph whose vertices are the protein's amino acids and whose edges are the interactions between them. Using a graph theory approach, we identify a number of properties of these networks. We compare them to the general small-world network model and we analyze their hierarchical structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Moreover, these four classes contain proteins of very different sizes, varying from several dozens to several thousands amino acids in SSE. The results obtained for the different classes are very similar, that is why in the rest of this section we show only the results for In a previous work (Gaci & Balev, 2008a), we have studied the two properties of SSE-IN related to the small-world model, namely their L/L RG and C/C RG ratios. Our results show (see Fig.…”
Section: Comparisons With the Small-world Networkmentioning
confidence: 77%
See 1 more Smart Citation
“…Moreover, these four classes contain proteins of very different sizes, varying from several dozens to several thousands amino acids in SSE. The results obtained for the different classes are very similar, that is why in the rest of this section we show only the results for In a previous work (Gaci & Balev, 2008a), we have studied the two properties of SSE-IN related to the small-world model, namely their L/L RG and C/C RG ratios. Our results show (see Fig.…”
Section: Comparisons With the Small-world Networkmentioning
confidence: 77%
“…Consequently, we identify a necessary condition for SSE-INs to be small-world, their average connected component size has to be less than 100. In (Gaci & Balev, 2008a) we show that the protein SSE-IN components interact with each other in the same way, no matter if they are small-world or not, see Fig 23. Then, it is interesting to study not the quantity of interaction inter-SSE but rather their quality, that is we want to put in evidence the role of nodes allowing interaction between different SSEs. In graph theory, the betweenness of a node is defined as the total number of shortest paths between pairs of nodes that pass through this node.…”
Section: Comparisons With the Small-world Networkmentioning
confidence: 78%
“…In previous works [8], [9], [11], we have studied the protein SSE-IN. We have identified notably some of their properties like the degree distribution or also the way in which the amino acids interact.…”
Section: Interaction Predictionmentioning
confidence: 99%
“…In [11] we have studied the quantity of edges between SSEs, also called shortcuts, and we have shown that it is bounded mainly due to the excluded volume effect. Nevertheless, even if the shortcut number can be estimated knowing its upper bound, the distribution of shortcuts between the different SSEs composing the sequence stays difficult to predict (actually it is too variable from one protein SSE-IN to another).…”
Section: Prediction Of the Edge Quantitymentioning
confidence: 99%
“…The roles played by proteins are varied and complex. Proteins are used for storage and transport of small molecules or ions and control the passage of molecules through the cell membranes essential for metabolic function [2]. Hormones, which transmit information and allow the regulation of complex cellular processes, are important regulators in responses to abiotic stress [3].…”
Section: Introductionmentioning
confidence: 99%